Principle of Thematic Correspondence in Dialogue of Official Letters (on Material of Citizens’ Appeals and Responses to Them) - T. V. Matveeva; M. A. Shirinkina (Научный диалог, 2019)
The article discusses text pairs of business letters (citizen appeal / official response). Within the framework of official correspondence as a special type of dialogical interaction, two texts with a single topic specified in the original letter are called a text pair. The aim is to substantiate the thematic correspondence of texts forming such a pair as a significant, though not the only, criterion of the quality of business reply letters. The detailed speech analysis of the material is carried out on the basis of the categorical-textual concept, according to which the category of the topic is expressed with the help of functionally identical names of the subject of speech (thematic chain), as well as their distributors. The preliminary stage of the analysis identifies and schematizes the composition of the thematic chains of the initial and response letters; the main stage is related to the comparison of the data obtained. The comparison of the thematic chains of the initial and response letters allows objectifying the conclusions about the degree of thematic correspondence of the texts that make up the pair. These conclusions are based on the analysis of the correlation of the main and additional thematic chains of the text, and most importantly - on the nature of the reproduction of the theme set in the address in the response official letter. It is argued that the thematic correspondence of paired business letters is a necessary minimum of quality business communication.